Hubungan Antara Fungsi Keluarga Dengan Post Partum Blues Pada Ibu Post Partum Di Wilayah Kerja Puskesmas Tladam Kecamatan Kawedanan Kabupaten Magetan - Rahayuningtyas, Faizah Betty; Megasari, Retwin Rahwanti (Jurnal Berita Ilmu Keperawatan, 2018)
The family is the smallest unit in society consisting of father, mother and child. In a family, there are five functions to be performed, such as affective function and coping, socialization function, reproductive function, the function of the economy, and health care function. There are several factors that can affect the function of the family, including employment, education, and economics. An agitated state of the mother and occurs after delivery characterized by feelings of sadness, crying, fear of taking care of the baby is called postpartum blues. The purpose of this study was to determine whether there is a relationship between family function with postpartum blues in the sub-district Puskesmas Tladan Kawedanan Magetan. The study design used is cross sectional analytic study, which means that the data collection is done in the period. The population in this study are pregnant women primigravida birth day forecast in April. These samples included 30 maternal postpartum with simple random sampling technique. The research instrument used to measure the Family APGAR questionnaire family function and EPDS questionnaire to measure postpartum blues. The measurement results were tested using the chi-square and p values obtained 0,024. P value less than 0.05 so it can be concluded that there is a correlation between family function with postpartum blues in the sub-district Puskesmas Tladan Kawedanan Magetan.